2003
DOI: 10.1017/s1472928803000074
|View full text |Cite
|
Sign up to set email alerts
|

Natural logarithmic relationship between brain oscillators

Abstract: Behaviorally relevant brain oscillations relate to each other in a specific manner to allow neuronal networks of different sizes with wide variety of connections to cooperate in a coordinated manner. For example, thalamo-cortical and hippocampal oscillations form numerous frequency bands, which follow a general rule. Specifically, the center frequencies and frequency ranges of oscillation bands with successively faster frequencies, from ultra-slow to ultra-fast frequency oscillations, form an arithmetic progre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
158
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 182 publications
(160 citation statements)
references
References 59 publications
1
158
0
1
Order By: Relevance
“…The ALFF values in the slow-5 band were higher in the primary sensory and motor areas (e.g., the primary somatosensory cortex, the precentral gyrus, the superior temporal gyrus, the paracentral lobule, and the supplementary motor area), the posterior part of the default-mode regions (e.g., the precuneus), and the anterior portion of the temporal lobe (e.g., the temporal pole), compared with the ALFF for the slow-4 band. According to previous studies, higher frequency fluctuations were confined to a small neuronal space, whereas very large networks were recruited during slow oscillations (Buzsaki and Draguhn 2004;Penttonen et al 2003). The ALFF in the slow-5 band involving larger brain regions provides evidence for the above statement.…”
Section: Differences In Alff Between Frequency Bandsmentioning
confidence: 57%
See 1 more Smart Citation
“…The ALFF values in the slow-5 band were higher in the primary sensory and motor areas (e.g., the primary somatosensory cortex, the precentral gyrus, the superior temporal gyrus, the paracentral lobule, and the supplementary motor area), the posterior part of the default-mode regions (e.g., the precuneus), and the anterior portion of the temporal lobe (e.g., the temporal pole), compared with the ALFF for the slow-4 band. According to previous studies, higher frequency fluctuations were confined to a small neuronal space, whereas very large networks were recruited during slow oscillations (Buzsaki and Draguhn 2004;Penttonen et al 2003). The ALFF in the slow-5 band involving larger brain regions provides evidence for the above statement.…”
Section: Differences In Alff Between Frequency Bandsmentioning
confidence: 57%
“…Previous rs-fMRI studies examining LFF amplitude have typically focused on the frequency band below 0.08 Hz due to its physiological significance. However, several studies have suggested that specific frequency bands may contribute differentially to LFF amplitude (Buzsaki and Draguhn 2004;Penttonen et al 2003;Zuo et al 2010). For example, the slow-4 band (0.027-0.073 Hz) exhibits higher LFF amplitude mostly in the basal ganglia, whereas the slow-5 (0.01-0.027 Hz) exhibits higher LFF amplitude mainly in cortical areas, such as in the prefrontal, parietal, and occipital cortices (Zuo et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…As a general rule, lower frequency oscillations allows for an integration of neuronal effects of longer duration and larger areas of involvement (Penttonen and Buzsaki, 2003). In contrast, high-frequency oscillations tend to be confined to small ensembles of neurons and facilitate a temporally more precise and spatially limited representation of information.…”
Section: A Physiological Description Of Neurofeedbackmentioning
confidence: 99%
“…Previously reported oscillation frequencies for these systems [8][9][10][11][12][13][14][15][16]20] are at least one order of magnitude slower than those observed here. We called such fast oscillations beta oscillations after the taxonomy adopted to classify rhythms of the brain [17]. The effect of temperature on the oscillation frequency is displayed in Table 1.…”
mentioning
confidence: 99%